Roadmap on inorganic perovskites for energy applications. (22nd July 2021) - Irvine, John; Rupp, Jennifer L. M.; Liu, Gang; Xu, Xiaoxiang; Haile, Sossina; Qian, Xin; Snyder, Alem; Freer, Robert; Ekren, Dursun; Skinner, Stephen; Celikbilek, Ozden; Chen, Shigang; et al.
Abstract: Inorganic perovskites exhibit many important physical properties such as ferroelectricity, magnetoresistance and superconductivity as well their importance as energy materials. Many of the most important energy materials are inorganic perovskites and find application in batteries, fuel cells, photocatalysts, catalysis, thermoelectrics and solar thermal. In all these applications, perovskite oxides, or their derivatives offer highly competitive performance, often state of the art and so tend to dominate research into energy material. In the following sections, we review these functionalities in turn seeking to facilitate the interchange of ideas between domains. The potential for improvement is explored and we highlight the importance of both detailed modelling and in situ and operando studies in taking these materials forward.